Oro de los Andes - Morán, María Rosa (2005)
This case study poses the problem of a mining company and their activities in the Ancash Department. Despite the vast quantity of natural and cultural resources in the region, the communities are not developed, lacking government services and access routes. In this context,the company decides to enact a program that would increase tourist activity, with the intention of generating more wealth in the region, and as a means to develop competitive advantages and a sustainable source of income and employment for the community.